Size effect mechanism of cross-section deformation and section hollow coefficient-bending degree of the thin-walled composite bending tube. (15th December 2021) - Zhu, Y.X.; Wan, M.M.; Wang, Y.; Tu, W.B.; Cheng, Y.F.
Graphical abstract: Highlights: Two dimensionless variables to describe the sectional dimensional characteristics. Restraint effect of covered tube increases deformation, the base tube is opposite. Mathematical model of size effect is product of double Boltzmann function. "Bendable forming zone" is distributed annularly around "un-formable zone" in space. Abstract: The composite tube has been widely used in various fields of piping systems, because of saving precious metals and combining physical and chemical properties of bi-material. There are important correlations between the bending forming accuracy and cross-section deformation mechanism of the composite tube, and its own size factors, that is the size effect. However, the correlations are not clear, and the effects of size factors are coupled or superimposed. Therefore, a brand-new research method of size effect is established. Two dimensionless variables of section hollow coefficient λ and bending degree w are introduced to describe the sectional dimensional characteristics. The mathematical model of size effect is established as well as the relationships between cross-section deformation Δ δ and λ, w and λ-w . Finally, the distribution of Δ δ in λ-w space has been developed based on the above research. The results are shown as follows. (1) All the relationships of Δ δ and λ - w can be described by the product of the double Boltzmann function, which is also the mathematical model of the size effect. (2) There are "un-formable zone", "bendable forming zone" and "best forming zone" of the composite tube in λ - w space. The "best forming zone" is Zb = λ, w |0.2 ≤ λ ≤ 0.58, 0.23 ≤ w ≤ 0.90.